Ukraine: ‘Callous disregard for human life’ of Russian forces’ response to Kakhovka dam destruction compounded by its disastrous effects upstream - Amnesty International (Amnesty International, 2023)
As the consequences of the Kakhovka dam destruction continue to unfold, the occupying Russian forces have been endangering lives in flood-afflicted areas following the destruction of the dam, while upstream water shortages and an upheaval of livelihoods point to an impending ecological and economic disaster, Amnesty International said today.
Ukraine
Keywords: 2023-06 June

Migrants’ rights defender from Russia convicted solely for her human rights work - Amnesty International (Amnesty International, 2023)
Tatyana Kotlyar is being punished simply for helping hundreds of people, including migrants and refugees, by generously registering them at her home.
Russian Federation
Keywords: 2023-06 June

Malta: Lives put at risk as parliament waters down bill seeking to partially decriminalize abortion - Amnesty International (Amnesty International, 2023)
The Maltese authorities’ decision to water down a version of a bill aimed at partially decriminalizing abortion in cases of grave risk to the life or health of pregnant people will endanger lives, Amnesty International said following the bills’ adoption by parliament.
Malta
Keywords: 2023-06 June

Eswatini: Authorities must stop using the courts to intimidate and harass union leaders - Amnesty International (Amnesty International, 2023)
Ahead of the court appearance of Sticks Nkambule, Secretary General of Swaziland Transport Communication and Allied Workers Union, on trumped-up charges of contempt of court stemming from his involvement in organizing a stay away action in December 2022, Vongai Chikwanda, Amnesty International’s Interim Deputy Director for Southern Africa, said: The harassment and intimidation of Sticks Nkambule shows that Eswatini authorities are effectively criminalizing peaceful dissent.
Eswatini
Keywords: 2023-06 June

Biden and Modi must address grave human rights concerns - Amnesty International (Amnesty International, 2023)
The United States and Indian governments must address the grave human rights issues in both countries during Prime Minister Modi’s meeting with President Biden in Washington DC, said Amnesty International ahead of the state visit this week.
India
Keywords: 2023-06 June

Stop harassing and arbitrarily arresting Afghans seeking refuge - Amnesty International (Amnesty International, 2023)
The situation of Afghan refugees in Pakistan is not receiving due international attention.
Pakistan
Keywords: 2023-06 June

Saudi Arabia: Imminent execution of seven young men would violate kingdom’s promise to abolish death penalty for juveniles - Amnesty International (Amnesty International, 2023)
Despite the Saudi authorities’ commitment to end their use of the death penalty against children under 18 at the time of the crime, seven young men are at risk of imminent execution after an appeals court confirmed their punishment, Amnesty International said today. Their execution would mark a chilling escalation of the already record-breaking use of the death penalty with the number of executions in the country having increased seven-fold in the past three years alone. “Saudi authorities have promised to limit the use of the death penalty and adopted legal reforms that prohibit the execution of people who were children at the time of the crime. If the authorities wish any of those promises to be taken seriously, they should order an immediate halt to the planned execution of the seven, who were all children at the time of their arrest,” said Heba Morayef, Amnesty International’s Middle East and North Africa Director.
Saudi Arabia
Keywords: 2023-06 June

The authorities of Senegal must immediately halt the police violence and restore social media - Amnesty International (Amnesty International, 2023)
Reacting to the violence that broke out yesterday in Dakar and other towns following the verdict in the trial of opposition leader Ousmane Sonko, Samira Daoud, Amnesty International’s Regional Director for West and Central Africa
Senegal
Keywords: 2023-06 June

Argentina must investigate crimes against humanity committed by Venezuelan authorities - Amnesty International (Amnesty International, 2023)
The Clooney Foundation for Justice has filed a lawsuit in Argentina's federal courts.
Argentina
Keywords: 2023-06 June